Faktor-Faktor Internal terhadap Pencegahan Fraud di BUMDES dengan Variabel Moral Sensitivity sebagai Moderasi - Nugroho, Aditya; Fahmi, Muhammad; Astarani, Juanda (Akuntansi & Ekonomika, 2024)
This research aims to analyze the influence of HR competency, whistleblowing, compliance with financial reporting, and internal control systems on fraud prevention in village-owned enterprises (BUMDES) management in Sungai Raya District, with moral sensitivity as the moderating variable. The research method used primary data and secondary data obtained through questionnaires. A sample of 85 respondents was selected using simple random sampling. The research results show that HR competency has a significant influence on fraud prevention, while whistleblowing does not have positive influence. Financial reporting compliance has a strong and significant connection with fraud prevention, while the internal control system does not have a significant connection. Apart from that, moral sensitivity is unable to moderate the influence of HR competency, whistleblowing, compliance with financial reporting, and internal control systems on fraud prevention by village-owned enterprises (BUMDES) managers.